The immunomodulatory effects of bevacizumab on systemic immunity in patients with metastatic melanoma - Mansfield, Aaron S. (Landes Bioscience, 2013)
Metastatic melanoma is near-to-invariably a fatal disease. As novel therapeutic strategies against metastatic melanoma are urgently needed, we have tested a combinatorial regimen consisting of conventional chemotherapy coupled to bevacizumab, a monoclonal antibody that inhibit angiogenesis, demonstrating some clinical benefit. A preliminary assessment of one of our clinical trials points to a previously unrecognized immunomodulatory effect of bevacizumab. Herein, we evaluate the immunomodulatory effect of bevacizumab when administered together with conventional chemotherapy to patients with metastatic melanoma. To this aim, we measured the abundance of various lymphocyte subsets among peripheral blood mononuclear cells (PBMCs) as well as the circulating levels of 42 cytokines, chemokines and growth factors in patients with metastatic melanoma who received albumin-bound paclitaxel plus carboplatin, either as a standalone intervention (AC, 55 subjects) or combined with bevacizumab (ACB, 39 individuals), in the context of clinical trials N057e and N0775, respectively. Relative shifts in PBMC subsets and cytokine levels were calculated (relative to baseline levels) when patients underwent restaging evaluation after two cycles of therapy. The Mann–Whitney U test was used to compare responses between the groups. Bevacizumab failed to affect the T(H)1/T(H)2 cell ratio in this patient cohort. However, we observed a significant increase in CD8(+) lymphocytes in patients who received ACB (+38%) but not in subjects treated with AC only (−10%) (p = 0.03). Moreover, circulating interleuikin-6 (IL-6) levels were reduced in patients treated with ACB (−42%) but not in individuals receiving AC only (28%) (p = 0.0018). Thus, the addition of bevacizumab to chemotherapy for the treatment of metastatic melanoma exerts immunomodulatory effects.